Nano-engineered hydrocolloid-based delivery systems for natural flavonoids: From structural diversity to bioavailability enhancement and therapeutic applications - Yueming Wang; Amin Zhang; Wenjie Chu; Chengliang Qi; Tianxing Zhou; Yu Pan; Yuhan Wang; Chengyang Wang; Yuan Liu; Wenli Wang (Food Hydrocolloids, 2027)

Astaxanthin activates PI3K/AKT and AMPK signaling to alleviate oxidative stress and improve mouse oocyte In vitro maturation - Mei Zhou; Mengzhen Luo; Yueming Yuan; Liqin Han; Lin Chen; Shangquan Gan (Theriogenology, 2026)

Abandoned farmland identification, reclamation potential assessment, and zonal management: A case study of Heshan City in China - Changsheng Xiong; Yueming Gao; Yumo Xing; Zhuo Xie; Tianxiao Zhou (Ecological Engineering, 2026)

Piston ventilation modulates thermal comfort in subway hubs via a dual-path coupling mechanism: A field study in Nanjing, China - Yuxuan Liu; Jiawei Leng; Yueming Wen; Haifei Zhou; Deqing Lin; Yuchong Qian (Building and Environment, 2026)

Remote sensing and statistical data integration for spatial discrimination and mapping of mariculture products: A case study of Sansha Bay - Jie Jiang; Xiaomei Yang; Yueming Liu; Zhihua Wang; Guo Yu; Dan Meng; Meiqi Zhou; Jialiang Liu (Ocean & Coastal Management, 2026)

Suppressing spectral broadening via intramolecular noncovalent interactions for high-efficiency solution-processed multi-resonance TADF OLEDs - Tao Zhou; Guimin Zhao; Yumiao He; Taiping Chen; Wenwen Tian; Yueming Sun; Wei Jiang (Chemical Engineering Journal, 2026)

Transforming from ‘natural tools’ into ‘custom sensors’: combining directionally designed biological nanopore electrochemistry sensing lumens with AI-driven analytics to pioneer a new paradigm for food analysis - Yanyang Yu; Yongfei Deng; Zhiyong Cui; Yueming Wang; Chenxi Zhang; Jinna Wang; Danni Zhang; Tianxing Zhou; Chuyue Gong; Shengli Zhang (Trends in Food Science & Technology, 2026)

Online monitoring of deposit-induced corrosion in a Waste-to-Energy boiler - Wenjie Liu; Yafang Wang; Yan Wang; Yongjun Liu; Anming Du; Qiongyu Ren; Xinran Zheng; Xiyu Chen; Minmin Zhou; Yueming Wang; Lunbo Duan (Waste Management, 2026)

An on-tissue parallel d0/d20-meladrazine derivatization approach for fatty acid peroxidation products imaging in adult zebrafish - Ji Yang; Yue Sun; Yueming Li; Zhonghua Wang; Zeper Abliz; Zhi Zhou (Analytica Chimica Acta, 2026)

Pharmacological inhibition of USP7 attenuates deltamethrin-induced neuronal ferroptosis via GPX4 stabilization - Minjia Wu; Yang Chen; Peixuan Ma; Wen Pan; Yaqin Deng; Lexing Wei; Guodong Lu; Michael Aschner; Yueming Jiang; Jing Zhou; Xiaowei Huang (Toxicology and Applied Pharmacology, 2026)

Non-linear interaction behavior of mixed industrial solid wastes in circulating fluidized beds: Reacting MP-PIC simulation - Minmin Zhou; Xiuzhi Wang; WenQiang Chen; Qiuchen Sun; DongFu Wang; Zhijiang Han; Chenxi Lu; Yueming Wang; Lunbo Duan; Wojciech P. Adamczyk (Fuel, 2026)

Electrochemical insights into the High-Temperature corrosion mechanism of 12Cr1MoV steel under Chlorine-Rich conditions - Yafang Wang; Wenjie Liu; Minmin Zhou; Wenxiu Yang; Dongfu Wang; Yueming Wang; Lunbo Duan (Fuel, 2026)

Umami_IP: An integrated model and explanatory analysis for quantitative prediction of Umami recognition threshold - Zhiyong Cui; Yueming Wang; Tianxing Zhou; Jiaming Gu; Zhiwei Zhang; Wenli Wang; Yuan Liu (Food Chemistry, 2025)

Porphyrin-heptazine framework photosensitizers for hypoxia-tolerant pyroptotic photo-immunotherapy via enhanced radical production - Debabrata Dutta; Yueming Xue; Qinghao Zhou; Yuanyuan Ji; Shikuo Li; Zhishen Ge (Chemical Engineering Journal, 2025)

The effects of gradient magnetic field on the detailed flow behavior of diffusion flames: Application for stabilizing coal bed methane flames - Hetong Gao; Yueming Wang; Minmin Zhou; Lunbo Duan (Fuel, 2025)

Gene flow network of four major pigments and role of LcmiR2111-KFB14 in pericarp browning of litchi during storage - Jiaqi Xiao; Shuting Zhang; Yijie Zhou; Xiangjin Kong; Hong Zhu; Yueming Jiang; Hongxia Qu (Postharvest Biology and Technology, 2025)

Simulated Study of a Multi-stage Permeable Reactive Barrier for In-Situ AMD Treatment of a Closed High-Sulfur Coal Mine - Yueming Qi; Pei Zhou; Dan Jiang; Lai Zhou; Yanzhuo Liu; Jiehui Zhang (Mine Water and the Environment, 2025)

MEK1 inhibition ameliorates mitochondrial-dependent apoptosis induced by deltamethrin in mouse hippocampal neuron HT22 cells - Lexing Wei; Yang Chen; Minjia Wu; Peixuan Ma; Huan Wang; Yueming Jiang; Michael Aschner; Jing Zhou; Guodong Lu; Lina Zhao; Xiaowei Huang (Toxicology in Vitro, 2025)

Synergistic impact of plant essential oil based microemulsion on lychee preservation in comparison to Prochloraz - Yujie Shen; Xin Zhou; Jupeng Zhao; Zhe Wang; Dandan Zhang; Lingrong Wen; Yueming Jiang; Liang Gong (Sustainable Chemistry and Pharmacy, 2025)

Tyr-Asp treatment delays senescence in litchi fruit by enhancing redox balance and maintaining energy homeostasis - Ruan Zhiyan; Yanxuan Zhu; Mengting Liu; Yijie Zhou; Xinguo Su; Yueming Jiang; Guoxiang Jiang (Postharvest Biology and Technology, 2025)

Corrigendum to ''Tyr-Asp enhances chilling tolerance in banana fruit by modulating redox homeostasis'' [Postharvest Biol. Technol., vol., 222, April 2025, 113338] - Yanxuan Zhu; Yiejie Zhou; Zhiwei Li; Ruimin Zhong; Yueming Jiang; Guoxiang Jiang; Xinguo Su (Postharvest Biology and Technology, 2025)

Transcription factor AcAGL9 and AcBEH1 synergistically regulate carotenoid biosynthesis during pineapple fruit ripening - Mengting Liu; Ting Li; Rufang Deng; Zhengke Zhang; Yijie Zhou; Xuewu Duan; Yueming Jiang; Guoxiang Jiang (Postharvest Biology and Technology, 2025)

Tyr-Asp enhances chilling tolerance in banana fruit by modulating redox homeostasis - Yanxuan Zhu; Yiejie Zhou; Zhiwei Li; Ruimin Zhong; Yueming Jiang; Guoxiang Jiang; Xinguo Su (Postharvest Biology and Technology, 2025)

High-performance flexible organic field-effect transistor based on highly ordered poly(3-hexylthiophene) nanowires - Liangkun Lu; Meng Si; Shaobo Jin; Zirui Zhao; Xuling Liu; Liguo Dai; Yueming Zhou; Hongjie Yang; Guoyong Ye (Chemical Engineering Journal, 2025)

Functional analysis of LcDORN1 genes in the senescence of litchi fruit - Yijie Zhou; Zhiwei Li; Xiangjin Kong; Jiaqi Xiao; Yueming Jiang; Xinguo Su; Hongxia Qu (Postharvest Biology and Technology, 2024)

Effect of Ba2+ on the biomineralization of Ca2+ and Mg2+ ions induced by Bacillus licheniformis - Huaxiao Yan; Xiaofei Zhu; Zhenjiang Li; Zhiyong Liu; Shengping Jin; Xiaotong Zhou; Zuozhen Han; Jusun Woo; Long Meng; Xiangqun Chi; Chao Han; Yanyang Zhao; et al. (World Journal of Microbiology and Biotechnology, 2024)

Identification of groundwater pollution sources and health risk assessment in the Fengshui mining area of Central Shandong, China - Hongyu Li; Jiaxin Wu; Yueming Qi; Chengzhi Su; Dan Jiang; Pei Zhou (Environmental Science and Pollution Research, 2024)

Benzotrithiophene-based covalent organic frameworks as efficient catalysts for artificial photosynthesis of H2O2 in pure water - Mingjie Liu; Peipei He; Hantao Gong; Zhenghua Zhao; Yueming Li; Kai Zhou; Yuemin Lin; Jing Li; Zongbi Bao; Qiwei Yang; Yiwen Yang; Qilong Ren; et al. (Chemical Engineering Journal, 2024)

CD137L Inhibition Ameliorates Hippocampal Neuroinflammation and Behavioral Deficits in a Mouse Model of Sepsis-Associated Encephalopathy - Fang Qiu; Yueming Liu; Yang Liu; Zhuyun Zhao; Lile Zhou; Pengfei Chen; Yunbo Du; Yanmei Wang; Huimin Sun; Changchun Zeng; Xiaokang Wang; Yuqiang Liu; et al. (NeuroMolecular Medicine, 2023)
Anxiety manifestations and cognitive dysfunction are common sequelae in patients with sepsis-associated encephalopathy (SAE). Microglia-mediated inflammatory signaling is involved in anxiety, depression, and cognitive dysfunction during acute infection with bacterial lipopolysaccharide (LPS). However, the molecular mechanisms underlying microglia activation and behavioral and cognitive deficits in sepsis have not been in fully elucidated. Based on previous research, we speculated that the CD137 receptor/ligand system modulates microglia function during sepsis to mediate classical neurological SAE symptoms. A murine model of SAE was established by injecting male C57BL/6 mice with LPS, and cultured mouse BV2 microglia were used for in vitro assays. RT-qPCR, immunofluorescence staining, flow cytometry, and ELISA were used to assess microglial activation and the expression of CD137L and inflammation-related cytokines in the mouse hippocampus and in cultured BV2 cells. In addition, behavioral tests were conducted in assess cognitive performance and behavioral distress. Immunofluorescence and RT-qPCR analyses showed that hippocampal expression of CD137L was upregulated in activated microglia following LPS treatment. Pre-treatment with the CD137L neutralizing antibody TKS-1 significantly reduced CD137L levels, attenuated the expression of M1 polarization markers in microglia, and inhibited the production of TNF-α, IL-1β, and IL-6 in both LPS-treated mice and BV2 cells. Conversely, stimulation of CD137L signaling by recombinant CD137-Fc fusion protein activated the synthesis and release of pro-inflammatory cytokines in cultures BV2 microglia. Importantly, open field, elevated plus maze, and Y-maze spontaneous alternation test results indicated that TKS-1 administration alleviated anxiety-like behavior and spatial memory decline in mice with LPS-induced SAE. These findings suggest that CD137L upregulation in activated microglia critically contributes to neuroinflammation, anxiety-like behavior, and cognitive dysfunction in the mouse model of LPS-induced sepsis. Therefore, therapeutic modulation of the CD137L/CD137 signaling pathway may represent an effective way to minimize brain damage and prevent cognitive and emotional deficits associated with SAE.

Effects of different high-temperature conduction modes on the ovalbumin-glucose model: AGEs production and regulation of glycated ovalbumin on gut microbiota - Haiqi Chen; Yanru Zhou; Siqiong Zhang; Zuohua Xie; Pingwei Wen; Hui Wang; Yueming Hu; Peihan Wu; Jiaojiao Liu; Qiannan Jiang; Zongcai Tu (Food Research International, 2023)

A viologen-based conductive hydrogel enables iontophoresis devices powered by Mg biobattery - Yan Zhou; Shan Jiang; Xuenan Ma; Yueming Mu; Jiaxin Zhao; Qin Liang; Xiaoteng Jia; Danming Chao (Chemical Engineering Journal, 2023)

Peroxymonosulfate activation by Ru/CeO2 for degradation of Triclosan: Efficacy, mechanisms and applicability in groundwater - Chaomeng Dai; Xueji You; Qian Liu; Yueming Han; Yanping Duan; Jiajun Hu; Jixiang Li; Zhi Li; Lang Zhou; Yalei Zhang; Shuguang Liu (Chemical Engineering Journal, 2023)

Passive ventilation for sustainable underground environments from traditional underground buildings and modern multiscale spaces - Yueming Wen; Siu-Kit Lau; Jiawei Leng; Kai Zhou; Shi-Jie Cao (Tunnelling and Underground Space Technology, 2023)

High-ratio {100} plane-exposed ZnO nanosheets with dual-active centers for simultaneous photocatalytic Cr(VI) reduction and Cr(III) adsorption from water - Xiao Li; Jiajia Liu; Jing Feng; Tong Wei; Zhongxiang Zhou; Jun Ma; Yueming Ren; Yanqing Shen (Journal of Hazardous Materials, 2023)

MaMYB13 is involved in response to chilling stress via activating expression of VLCFAs and phenylpropanoids biosynthesis-related genes in postharvest banana fruit - Zhiwei Li; Yijie Zhou; Hanzhi Liang; Qing Li; Yueming Jiang; Xuewu Duan; Guoxiang Jiang (Food Chemistry, 2023)

Degradation of water-soluble polysaccharides in pulp of litchi during storage - Zhongsuzhi Chen; Meiying He; Yijie Zhou; Xi Chen; Hong Zhu; Bao Yang; Yueming Jiang; Hongxia Qu (Food Chemistry, 2023)

Prenylated flavonoids in foods and their applications on cancer prevention - Lingrong Wen; Ting Zhou; Yueming Jiang; Sui Kiat Chang; Bao Yang (Critical Reviews in Food Science and Nutrition, 2022)

The Impact of Multiple Pond Conditions on the Performance of Dike-Pond Extraction - Jinhao Zhou; Wu Zhou; Qiqi Zhou; Yuanhui Zhu; Fei Xie; Shen Liang; Yueming Hu (Fishes, 2022)
Dike-ponds in fisheries often present multiple pond conditions such as pure, suspended sediment, water bloom, semidry conditions, etc. However, the impact of these conditions on the performance of extracting dike-pond from remote sensing images has not been studied. To solve this problem, we explore the existence of such impacts by comparing the performance of four rule-based methods in two groups of test regions. The first group has few multiple pond conditions, while the second has more. The results show that various measure values deteriorate as the proportion of multiple pond conditions in the regions increases. All four methods performed worse in the second group than the first, where the overall accuracy decreased by 8.80%, misclassification error increased by 3.69%, omission error raised by 10.53%, and correct quantity rate dropped by 8.23%, respectively. The extraction method that ingested multiple pond conditions performed indistinguishably from the other methods in the first group. However, it outperformed the other methods in the second group, with a 4.22% improvement in overall accuracy, a 10.25% decrease in misclassification error, and a 19.03% increase in the correct quantity rate. These findings suggest that multiple pond conditions can negatively impact the extraction performance and should be considered in dike-pond applications that require a precise pond size, number, and shape.

Establishment of Galectin-3 Time-resolved Fluoroimmunoassay and its Application in Idiopathic Membranous Nephropathy - Xiaomei Yu; Lingli Chen; Bo Lin; Li Zhang; Xue Yang; Xiaobin Liu; Pengguo Xia; Yueming Liu; Shaoxiong Zheng; Xiumei Zhou; Yigang Wang; Yuan Qin; et al. (Journal of Fluorescence, 2022)

Safety and efficacy of new oral anticoagulants compared to those of warfarin in AF patients with cancer: a meta-analysis of randomized clinical trials and observational studies - Yueming Chen; Min Mao; Jing Chang; Jing Yan; Tiantian Yang; Yang Liu; Meng Luo; Yuhao Hu; Qi Yang; Lin Zhou; Kanghua Ma (European Journal of Clinical Pharmacology, 2021)

ATP-binding cassette g1 regulates osteogenesis via Wnt/β-catenin and AMPK signaling pathways - Lei Zhou; Shiwei Sun; Tieqi Zhang; Yueming Yu; Liang Xu; Haoran Li; Minghai Wang; Yang Hong (Molecular Biology Reports, 2020)

Cholesterol 25-hydroxylase suppresses rabies virus infection by inhibiting viral entry - Yueming Yuan; Zongmei Wang; Bin Tian; Ming Zhou; Zhen F. Fu; Ling Zhao (Archives of Virology, 2019)

The Adsorption Behavior of Pb2+ and Cd2+ in the Treated Black Soils with Different Freeze-Thaw Frequencies - Xu Wang; Yueming Li; Na Mao; Yanqiu Zhou; Ping Guo (Water, Air, & Soil Pollution, 2017)